Selametan (Salvation) Tradition in Islam Overview - Nanik Mindarnengsih (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
Islam religion is the biggest religion in Indonesia and the most adhered with 87.2% of population. Islam in Indonesia is roughly considered to have gradually spread through merchant activities by Arab Muslim traders, adoption by local rulers and the influence of mysticism since the 13th century. This research uses descriptive method to explain data collection in the field, which provides an overview of Selametan (Salvation) Tradition in Islam overview. Research approach uses a anthropolgy qualitative approach. Data are written results from interviews, observation, and documentations in Salvation Tradition. Data sources are from Javanese People. The results of this research mentions that Salvation Tradition is a good tradition about praying attitude of khudhu' and khusyu' to Allah but It must be followed with traditional ceremony based on the Javanese Ancestors. Research focus is related with Islam overview that Islam does not teach about Salvation in order to get bless from ancestor. From the statement above, Islam believes that getting bless can be done by making Qur’an recitation as anual event. Keywords: Religion, Islam, Salvation, Selametan, Tradition, Qualitative Approach, Recitation, Overview.